A simplified approach to establishing the impact of software source code changes on requirements specifications - Mugambi Muthengi, Fredrick; Muchangi Mugo, David; Makau Mutua, Stephen; Mueni Musyoka, Faith (Institute of Advanced Engineering and Science, 2025)
This paper proposes an improved approach to establishing the impact of source code changes in software features. An association of the methods affected by the changes made and functional requirements of the software reveals the likely impact of the changes made in the software. Changes in source code are exhibited in the operational behaviour of the software. Functional requirements and source code artefacts play a key role in assessing the impact of the changes made. In this study, we investigated the possibility of establishing the association between the changed methods and the functional requirements. The study found out that changes made in the methods can be mapped to the functional requirements that the methods are implementing. The motivation in this endeavour was to assess the impacted software requirements which translate to the likely software features affected by the changes made in the software. With the intent of the software users being seen in the requirements statements and the method naming by the developers, a mapping of the two software artefacts would help developers find out the impacted software features when assessing the overall effect of the committed changes.